Uslūb al-Kināyah Kaẓāhirah Uslūbīyah Hāmah Fī al-Qur’an al-Karīm - Sukamto Said (Al-Jami'ah Research Centre, 2001)
One of the miracles of Qur'an is its wording. Qur'an was revealed in Arabic for the people who had a great on language aesthetics (literature) to convey the message and use various literaly styles. One of them is kinayah. This article examines the issue of the literary style in Qur'an' kinayah, which is multipurpose. It can be used to depict either human interest or godhead. Kinayah is used, among other things, because of the restriction on language to express certain ideas. As a holy book for human that is valid forever, Qur'an uses kinayah to create new meanings, because the characteristic of kinayah is its possibility to be undersiood from